COACHeD RCT Additional Files 2021 - Holbrook, Anne (N/A, 2021)
Introduction: Oral anticoagulants (OACs) are very commonly prescribed, have well documented benefits for important clinical outcomes but have serious harms as well. OAC-related thromboembolic and hemorrhagic event rates are especially high shortly after hospital discharge. Expert OAC management involving virtual care is a research priority given its potential to reach far-flung communities in a more convenient, physically distanced and less costly way than in-person care. Objective: To test whether a focused, expert medication management intervention using a mix of in-person consultation and virtual care follow-up, is feasible and might be effective in preventing anticoagulation-related adverse events, for patients transitioning from hospital to home. Methods and Analysis: A randomized parallel multicentre design enrolling consenting adult patients or the caregivers of cognitively impaired patients about to be discharged from medical wards with a discharge prescription including an oral anticoagulant. The interdisciplinary intervention is led by a clinical pharmacologist and includes a detailed discharge medication reconciliation and management plan focused on oral anticoagulants at hospital discharge; a circle of care handover and coordination with patient, hospital team and community providers; early post-discharge follow-up virtual medication check-up visits at 24 hours, 1 week, and 1 month with triage of any problems. The control group will receive usual care plus encouragement to use Thrombosis Canada website. Co-primary outcomes include a) feasibility such as recruitment rate, participant retention rates, trial resources management, and b) clinical outcomes primarily adverse anticoagulant safety events composite (AASE), coordination and continuity of care, medication-related problems, quality of life and health resource utilization. Follow-up is 3 months.
Additional files include: Coordination and Continuity of Care Questionnaire, Patient Knowledge of OAC Management Quiz, and the Patient/Caregiver Study Satisfaction Survey.
Keywords: OAC Management; Randomized control trial; continuity of care